Pendekatan Multi, Inter dan Transdisiplin dalam Integrasi Agama dan Sains - Nazifa, Mahda Naura; Muhammad, Amril; Dewi, Eva; Rahmadhani, Saszlin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This article discusses the Multi, Inter, Transdisciplinary Approach in the Integration of Religion and Science. This research uses the library research method. Library research is a type of research whose main data is sourced from books, journals, or articles. This research highlights the emergence of various problems along with the development of the times whose solutions can use various different approaches, in this case discussing the Multi, Inter and Transdisciplinary approaches in the integration of religion and science. The result of this research is that multi, inter, and transdisciplinary approaches have the potential to produce a comprehensive and deeper understanding and are able to provide more holistic solutions to today's complex problems.